O ofício do psicanalista - Couto, Richard (Percurso, 2010)
Resenha de S. Alberti, W. Amendoeira, E. Lannes, A. Lopes, A. e E. Rocha (orgs.), Ofício do psicanalista: formação vs. regulamentação, São Paulo: Casa do Psicólogo, 2009, 197 p.